2021
DOI: 10.1182/blood.2020009362
|View full text |Cite
|
Sign up to set email alerts
|

Posttransplant cyclophosphamide is associated with increased cytomegalovirus infection: a CIBMTR analysis

Abstract: Prior studies suggest increased CMV infection following haploidentical donor transplantation with post-transplant cyclophosphamide (HaploCy). The role of allograft source and PTCy in CMV infection and disease is unclear. We analyzed the effect of graft source and PTCy on incidence of CMV infection as well as transplant outcomes as it relates to CMV serostatus and occurrence of CMV infection by d180. We examined patients reported to CIBMTR between 2012-2017 who had received HaploCy (n = 757), Sib with PTCy (Sib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(73 citation statements)
references
References 51 publications
3
69
1
Order By: Relevance
“…21,22 Recently, CIBMTR published an analysis comparing the incidence and impact of CMV infection in 757 patients who received haplo-HSCT with and demonstrated that PTCy, regardless of donor, is associated with higher incidence of CMV infection and, among those developing CMV infection, haplo-HSCT had worse OS and NRM. 23 The intense immunosuppression used in both types of transplants may explain these findings.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Recently, CIBMTR published an analysis comparing the incidence and impact of CMV infection in 757 patients who received haplo-HSCT with and demonstrated that PTCy, regardless of donor, is associated with higher incidence of CMV infection and, among those developing CMV infection, haplo-HSCT had worse OS and NRM. 23 The intense immunosuppression used in both types of transplants may explain these findings.…”
Section: Discussionmentioning
confidence: 99%
“…PTCy, regardless of donor, was associated with a higher incidence of CMV infection. The study also concluded that CMV infection could negate the cGVHD protective benefit of PTCy ( 75 ).…”
Section: In the Haematological Settingmentioning
confidence: 99%
“…PTCy is a method of in vivo T cell depletion that mainly acts on alloreactive T cells after haploSCT. CMV reactivation was noticed in 42%-69.2% of patients who underwent PTCy-haploSCT (51)(52)(53)(54)(55)(56)(57)(58). A total of 2.8%-4.5% of patients experienced CMV-associated disease (51,52).…”
Section: Ptcy-haplosctmentioning
confidence: 99%
“…CMV reactivation was noticed in 42%-69.2% of patients who underwent PTCy-haploSCT (51)(52)(53)(54)(55)(56)(57)(58). A total of 2.8%-4.5% of patients experienced CMV-associated disease (51,52). CMV reactivation occurred at a median time of 35-39 days (51,52,57).…”
Section: Ptcy-haplosctmentioning
confidence: 99%